Management of Helicobacter pylori infection by clinicians: A nationwide survey in a developing country. Issue 6 (1st October 2019) - Song, Conghua; Xie, Chuan; Zhu, Yin; Liu, Wenzhong; Zhang, Guoxin; He, Shuixiang; Zheng, Pengyuan; Lan, Chunhui; Zhang, Zhenyu; Hu, Renwei; Du, Qin; Xu, Jianming; et al.
Abstract: Background & Aims: Developing countries are making efforts to improve health management. Practice deviating from the guideline means inefficient control. The study aims to investigate the management of Helicobacter pylori ( H pylori ) infection from a developing country perspective. Methods: An authoritative survey was conducted in 14th (2014) and 17th (2017) Congress of Gastroenterology China, respectively. The Maastricht V/Florence consensus report was invoked as the evaluation criterion. Results: A total of 4182 valid samples were included in this study. Most of the respondents (94%) updated knowledge by lectures. Respondents had a different awareness rate of H pylori ‐related diseases, ranging from 45% to 95%. Up to 40% of the respondents did not follow the recommendations for the diagnosis. Choice accuracy of eradication regimens and antibiotic combinations was <70%. About 20% of the respondents did not pay attention to the confirmation after the eradication. The situation had been improved in 2017 when compared with that in 2014 (all P < .05). Multivariate logistic regression analysis revealed that influencing factors including nongastroenterologists, bachelor degree and below, the primary professional title, hospital location, and a small proportion of H pylori infection in daily practice related to the deviation of consensus (all P < .05). Conclusions: Although the management of H pylori infection has been improved in a developing country, there is still a gap between the real‐world practices and the consensus. Influencing factors should be taken into account in decision‐making, and the corresponding population should be strengthened with precision training during the promotion of the guideline.